Faith and Ethnicity : Volume 1 - Borght, van der,; Keulen, Dirk van,; Brinkman, Martien, (Studies in Reformed Theology;, 2002)
In writing 'In Christ there is neither Jew nor Greek', the apostle Paul touched on a topic that still is hotly debated among christians today: the relationship between faith and ethnicity. The Reformed Churches, usually organised along regional or national lines, are no exception and wrestle world-wide with the issue. This volume offers Asian and African perspectives, especially exploring the Indonesian and South African context. This and the next volume of Studies in Reformed Theology contain contributions to the fourth international conference of the International Reformed Theological Institute (IRTI), held in Princeton, N.J., U.S.A. (2001), on the theme of Faith and Ethnicity.